Strategic management and considerations for the use of Ukraine's natural resources in conditions of war and opportunities for peace: obstacles and risks - Olha Viunyk; Iryna Bosak; Mariya Vashchyshyn; Olena Morozova (Clío)
The large-scale war in Ukraine, caused by Russia's full-scale invasion in February 2022, has generated unusual consequences for Ukraine and for the world order. In this context, the overall objective of this research is to analyze the objective and subjective conditions that determine the Strategic Management of Ukraine's natural resources in the current war context, evaluating in the process geostrategic considerations and opportunities for sustainable peace, to project future scenarios that identify risks, obstacles and enabling factors in the process of national reconstruction. Methodologically, we worked with a design of critical observation of documentary sources, which were selected under the criterion of their recognized academic value. It is concluded that environmental and natural resource governance has the potential to facilitate peace-building processes in post-conflict contexts through three key mechanisms: promoting contact between opposing parties; fostering interdependence; and developing institutional capacity for conflict management.